Cost analysis in favor of a combined approach for cytomegalovirus after kidney transplantation: a single‐center experience. Issue 1 (23rd November 2012) - Hellemans, R.; Beutels, P.; Ieven, M.; Verpooten, G.A.; Bosmans, J.L.
Abstract Background In kidney transplant recipients, cytomegalovirus (CMV) can cause significant morbidity, mortality, and costs, which can be prevented by universal antiviral prophylaxis or preemptive therapy. Methods With the aim to improve our understanding of the advantages and disadvantages of these interventions, we documented resource use for 101 consecutive kidney transplant recipients in our center receiving preemptive therapy and estimated resource use for 2 alternative scenarios. Results At 100 days after transplantation, the mean total costs of our preemptive strategy including monitoring and treatment with intravenous ganciclovir was €2545 per patient. At €4853 per patient, these costs were highest for the CMV‐positive donor/CMV‐negative recipient (D+/R−) patient subgroup (n = 28), who frequently require recurrent treatment. A treatment scenario with valganciclovir prophylaxis for D+/R− and R+ patients, in which we ignored late‐onset disease after discontinuation of prophylaxis, resulted in an estimated cost of €1892 per patient. A combined approach using valganciclovir prophylaxis in the D+/R− group and a preemptive strategy in the R+ groups would result in the lowest mean and median costs per patient (€1701). Conclusion Our study suggests that a combined approach, using valganciclovir prophylaxis in D+/R− patients and preemptive treatment in R+ patients, may result in the lowest cost. This approach seems reasonable as it restricts expensive prophylactic drug therapy to those who would benefit the most, whereas it limits the risk for drug toxicity and late‐onset disease in those at lower risk for CMV.